The Social Psychology of Inequality 2019
DOI: 10.1007/978-3-030-28856-3_10
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Consequences of Inequality for Food Intake

Abstract: How is inequality associated to social gradients in health such as obesity? Inconclusive findings and misunderstanding regarding the association between inequality and obesity impair attempts to reduce social gradients in obesity. In this chapter we discuss various findings from research on food choices and consumption in situations broadly associated with inequality; that is, environmental scarcity and resource competition, relative deprivation and wealth, and social class distinctions. Based on a review of s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 110 publications
(109 reference statements)
0
3
0
Order By: Relevance
“…Yet, in the wider context of aiming to understand the link between societal inequality and unhealthy diets, it may appear questionable whether feelings of unfairness is a relevant additional process as compared to the mere upward social comparison process. Previous studies have shown that upward social comparisons without feelings of unfairness per se influenced unhealthy eating behaviour [ 35 , 36 ]. For example, people that perceived to have a lower relative income than their interaction partners consumed more calories [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yet, in the wider context of aiming to understand the link between societal inequality and unhealthy diets, it may appear questionable whether feelings of unfairness is a relevant additional process as compared to the mere upward social comparison process. Previous studies have shown that upward social comparisons without feelings of unfairness per se influenced unhealthy eating behaviour [ 35 , 36 ]. For example, people that perceived to have a lower relative income than their interaction partners consumed more calories [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fifth, in Study 3, the sample consisted of women only and so its findings cannot be generalized to men. Yet, studying a female population may be especially relevant, as the social status and BMI relationship has been more consistently found among women than among men [ 35 , 36 , 75 ]. Future research on PRD and dietary outcomes may need to identify any differential effects for gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation